Village Government Programs in Developing Qur'an Reading in Bulungihit Village, Marbau Sub-district - Suriyanti Suriyanti; Muaz Tanjung (LPPM Universitas Trunojoyo Madura, 2023)
Al-Qur'an is a way of life for Muslims, if it is abandoned then it will get lost, so it is a must for Muslims to learn and read Al-Qur'an. However, it is very unfortunate that children's interest in learning to read the Qur'an is very much this has resulted in very many adults who are still unable to read the Qur'an (illiterate). To deal with this problem, a Koran Reading Development Program was held, which is a program held by the Bulungihit Village Government through reciting activities with Ustadz/Ustadzah and teaching and learning at Madrasah Ibtidaiyah. Children can get the most out of learning how to read the Al-Qur'an properly and correctly. . This study uses a qualitative method with interview techniques where the research conducts questions and answers to several community leaders such as the village head, hamlet head, MDA school head, and Ustadz/ustadzah to collect data. Based on the results of the study, it is explained that the Village Government Program is running well and experiencing developments in each period, this is enough to explain that the role played by the government is very real and sustainable. Supervision continues to be carried out routinely through reports that are made every month. With this, the program can be declared a success and the children's interest in learning to read the Qur'an is increasing and printing the recitations of the Qur'an.